Effective elimination of bacteria on hard surfaces by the combined use of bacteriophages and chemical disinfectants - Zongyue Chen; Yuhui Yang; Gaoming Li; Youying Huang; Yu Luo; Shuai Le (Microbiology Spectrum, 2024)
ABSTRACTHospital-acquired infections (HAIs) represent one of the significant causes of morbidity and mortality worldwide, and controlling pathogens in the hospital environment is of great importance. Currently, the standard disinfection method in the hospital environment is chemical disinfection. However, disinfectants are usually not used strictly according to the label, making them less effective in disinfection. Therefore, there is an emergent need to find a better approach that can be used in hospitals to control pathogenic bacteria in the clinical environment. Bacteriophages (phages) are effective in killing bacteria and have been applied in the treatment of bacterial infections but have not received enough attention regarding the control of contamination in the clinical environment. In this study, we found that various phages remain active in the presence of chemical disinfectants. Moreover, the combined use of specific phages and chemical disinfectants is more effective in removing bacterial biofilms and eliminating bacteria on hard surfaces. Thus, this proof-of-concept study indicates that adding phages directly to chemical disinfectants might be an effective and economical approach to enhance clinical environment disinfection.IMPORTANCEIn this study, we investigated whether the combination of bacteriophages and chemical disinfectants can enhance the efficacy of reducing bacterial contamination on hard surfaces in the clinical setting. We found that specific phages are active in chemical disinfectants and that the combined use of phages and chemical disinfectants was highly effective in reducing bacterial presence on hard surfaces. As a proof-of-concept, we demonstrated that adding specific phages directly to chemical disinfectants is an effective and cost-efficient strategy for clinical environment disinfection.